Micropolar Couple Stress Nanofluid Flow by Non-Fourier’s-Law Heat Flux Model past a Stretching Sheet - Gosa Gadisa; Tagay Takele; Shibiru Jabessa (Journal of Mathematics)
In this investigation, thermal radiation effect on MHD nonlinear convective micropolar couple stress nanofluid flow by non-Fourier’s-law heat flux model past a stretching sheet with the effects of diffusion-thermo, thermal-diffusion, and first-order chemical reaction rate is reported. The robust numerical method called the Galerkin finite element method is applied to solve the proposed fluid model. We applied grid-invariance test to approve the convergence of the series solution. The effect of the various pertinent variables on velocity, angular velocity, temperature, concentration, local skin friction, local wall couple stress, local Nusselt number, and local Sherwood number is analyzed in both graphical and tabular forms. The range of the major relevant parameters used for analysis of the present study was adopted from different existing literatures by taking into consideration the history of the parameters and is given by 0.07≤Pr≤7.0,0.0≤λ,ε≤1.0,0.0≤Rd,Df ,Sr,K,≤1.5,0.0≤γE≤0.9,0.9≤Sc≤1.5,0.5≤M≤1.5,0.0≤β≤1.0,0.2≤Nb≤0.4,0.1≤Nt≤0.3. The result obtained in this study is compared with that in the available literatures to confirm the validity of the present numerical method. Our result shows that the heat and mass transfer in the flow region of micropolar couple stress fluid can be enhanced by boosting the radiation parameters.